Pengaruh Perhatian Orang Tua Terhadap Pembimbingan Akhlak Pada Anak Dalam Keluarga di Desa Pagar Agung Kelurahan Tanjung Agung Kecamatan Pagar Alam Selatan - Salwa aurumia firanti; Meleza Andora; Hartatiana; Muhammad Win Afgani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the influence of parental attention on moral guidance for children in families in the village of Pagar Agung, Tanjung Agung Subdistrict, South Pagar Alam District. The purpose of this study is to determine whether or not there is an influence of parental attention on moral guidance for children in families in the village of Pagar Agung, Tanjung Agung Subdistrict, South Pagar Alam District, and to determine how parental attention influences moral guidance for children in families in Pagar Agung Village, Tanjung Agung Subdistrict, Pagar Alam Selatan District, as well as to determine the moral character of children in families in Pagar Agung Village, Tanjung Agung Subdistrict, Pagar Alam Selatan District, with a sample of 50 parents and 50 children. This study used a quantitative research method. The analysis technique used was simple linear regression analysis with data processing assisted by the SPSS version 29 program. The results of the analysis showed a positive and significant effect on children's moral guidance in Pagar Agung Village, Tanjung Agung Subdistrict, Pagar Alam Selatan District.